2021
DOI: 10.3390/ijms22147584
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Receptor Reserve and Long-Term Potentiation: Unconventional Adaptive Mechanisms in Cardiovascular Diseases?

Abstract: While the concept of a receptor reserve (spare receptors) is old, their presence on human cells as an adaptive mechanism in cardiovascular disease is a new suggestion. The presence of spare receptors is suspected when the activation of a weak fraction of receptors leads to maximal biological effects, in other words, when the half-maximal effective concentration (EC50) for a biological effect (cAMP production, for example) is lower than the affinity (KD) of the ligand for a receptor. Adenosine is an ATP derivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 89 publications
0
6
0
Order By: Relevance
“…These observations underline the importance of research efforts aiming an understanding of heart physiology and pathophysiology, with special emphasis on interspecies differences. An important topic in this field is the investigation of endogenous cardioprotective mechanisms such as the cardiac adenosinergic system [ 3 , 4 , 5 , 6 ], a system in which species dependence is also present [ 7 ]. Of course, in the usual sequence of information acquisition in life sciences, animal experiments will precede human studies for a long time to come.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations underline the importance of research efforts aiming an understanding of heart physiology and pathophysiology, with special emphasis on interspecies differences. An important topic in this field is the investigation of endogenous cardioprotective mechanisms such as the cardiac adenosinergic system [ 3 , 4 , 5 , 6 ], a system in which species dependence is also present [ 7 ]. Of course, in the usual sequence of information acquisition in life sciences, animal experiments will precede human studies for a long time to come.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, adenosine is a substrate for several enzymes and transporters [8,9]. CHA (N 6 -cyclohexyladenosine) and CPA (N 6 -cyclopentyladenosine) are synthetic adenosine analogues that act as selective, biologically stable (enzyme-resistant, especially CHA [10]) and high-efficacy (especially CPA [11]) full agonists for the A 1 adenosine receptor (A 1 receptor). The A 1 receptor is the predominant adenosine receptor type of the myocardium that mediates several protective processes including negative tropic effects (primarily on the supraventricular myocardium) [8,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the presence of spare receptors in this population was associated with a low adenosine plasma concentration level and mainly with negative HUT [40]. Yet, it was postulated that the presence of spare receptors could be an adaptive mechanism to low agonist concentration levels, low receptor production levels or both [42,43].…”
Section: Role Of Adenosinergic System In Nhsmentioning
confidence: 89%
“…This last dimension is named K D (affinity constant), while the concentration of agonists necessary to obtain half of the maximal biological effects is named EC 50 . Thus, from a practice point of view, the presence of receptor reserves is evidenced by a high K D /EC 50 ratio [42,43]. Specific tools are necessary to evaluate the presence of spare receptors.…”
Section: Role Of Adenosinergic System In Nhsmentioning
confidence: 99%
“…Moreover, under A2BR deficiency, a mouse ischemic heart model showed an increased number of immune cells, including B cells, NK cells, and CD4 T-cells. Additionally, A2BR plays an important role in the proliferation, differentiation, and apoptosis of cancer cells ( Guieu et al, 2021 ; Augustin et al, 2022 ). Generation of purine nucleosides in TME effectively inhibits T-cell and NK cell activities, studies have found that A2AR and A3R play critical roles in tumor immune responses ( Zahavi & Hodge, 2023 ; Strickland et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%